Partisipasi pendidikan Kristiani di ruang publik dalam menunjang deradikalisasi - Wowor, Jeniffer Pelupessy (KURIOS (Jurnal Teologi dan Pendidikan Agama Kristen), 2021)
This article highlights the issue of radicalism that is rife in Indonesia today. Deradicalization is seen as an effort that can be taken to overcome this problem. This paper presents the realization of this strategy from Christian Education's perspective. A qualitative approach through analysis of written materials in literature study is presented in this paper. In particular, the research results from the discourse analysis study of news papers that have been carried out previously are used along with some supporting works of literature to complement the required analysis data. Jack L. Seymour's ideas about the importance of a holistic approach in Christian Education, including a faith community approach, instructional and missional, are the theoretical basis in this paper. These three approaches are correlated with the concept of public theology. As a result, Christian education for encouraging people in the public sphere has become a transformational approach to present the benefits of faith education in the public sphere, primarily to support the deradicalization process. Abstrak Tulisan ini menyoroti persoalan radikalisme yang marak di Indonesia saat ini. Deradikalisasi dipandang sebagai salah satu upaya yang dapat ditempuh dalam mengatasi persoalan ini. Tulisan ini mengetengahkan realisasi dari strategi ini dalam perspektif Pendidikan Kristiani. Dengan menggunakan pendekatan kualitatif melalui jenis penelitian literatur, analisis bahan tertulis dipaparkan dalam tulisan ini. Secara khusus hasil penelitian dari kajian analisis wacana atas surat kabar yang telah dilakukan sebelumnya beserta tambahan beberapa literatur penunjang disuguhkan untuk melengkapi data analisis. Gagasan Jack L. Seymour tentang pentingnya pendekatan holistik dalam Pendidikan Kristiani yang meliputi pendekatan komunitas iman, instruksional dan misi menjadi landasan teori dalam tulisan ini. Ketiga pendekatan ini dikorelasikan dengan kajian teologi publik. Hasilnya, partisipasi pendidikan Kristiani di ruang publik menjadi sebuah bentuk pendekatan transformasional dalam upaya untuk menghadirkan manfaat pendidikan iman pada ruang publik, khususnya dalam menunjang proses deradikalisasi.